Rapid quantitative detection of Vibrio parahaemolyticus via high-fidelity target-based microfluidic identification. (December 2022) - Xiang, Xinran; Diao, Enjie; Shang, Yuting; Song, Minghui; He, Yinglong
Graphical abstract: Highlights: A microfluidic recognition strategy (HFTMI) based on high fidelity target is proposed. Applying the HFTMI strategy to rapidly identify Vibrio parahaemolyticus . Optimizing the injection system of digital chip. The LOD of HFTMI strategy for are 10 2 CFU·mL −1 in spike sample within 30 min. The strategy shows excellent practical performance in natural food samples. Abstract: With the rapid development of logistics, a growing number of pathogenic microorganisms has the means to spread worldwide using food as a carrier; thus, there is an urgent need to develop effective detection strategies to ensure food safety. By combining novel markers identified by pan-genome analysis and a digital recombinase-aided amplification (RAA) detection method based on a microfluidic chip, a strategy of high-fidelity target-based microfluidic identification (HFTMI) has been developed. Herein, a proof-of-concept study of HFTMI for rapid pathogen detection of V. parahaemolyticus was investigated. Specific primers designed for the gene group_41170 identified in the pan-genome analysis showed high sensitivity and a broad spectrum for the detection of V. parahaemolyticus . Different power systems were investigated to increase the partition rate on specifically designed chamber-based digital chips. The performance of HFTMI was greatly improved compared with qPCR. Collectively, this novel HFTMI system provides more reliable guidance for food safety testing.